KLASIFIKASI DATA BADAN USAHA MILIK DESA (BUMDES) DALAM PENERIMAAN BANTUAN DI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA PROVINSI BENGKULU - Pane, Majid Karim; Siswanto, Siswanto; Supardi, Reno (UNIVED Press, 2021)
The Bengkulu Province Community and Village Empowerment Service will collect data on Village-Owned Enterprises (BUMDES) in Bengkulu Province every period. Apart from data collection, the Department will usually provide assistance funds for BUMDES that meet the requirements that have been set, namely there is a PERDES regarding the formation of BUMDES, active management, the business is running, there is an AD/ART, there is a bank account, there is a NPWP, and there is a cover letter. from the Regency DPMD Application for Data Classification of Village-Owned Enterprises (Bumdes) in Receiving Assistance at the Community and Village Empowerment Service of Bengkulu Province is an application that can be used to determine the feasibility of Bumdes by analyzing test data (next year's data) based on parameters from training data (data previous year). Classification is divided into 2 classes, namely Eligible and Not Eligible. The method used in classifying Village-Owned Enterprises (Bumdes) data in receiving aid is the Naive Bayes method. The training data will be analyzed first in order to find out the number and probability, where these values ​​will be used to calculate the final value of the test data. The assessment parameters used in the application are Village Regulation, Active Management, Business Already Running, AD ART, Bank Account, and NPWP. The training data was taken from 2018 while the test data was taken from 2019. The Data Classification Application for Village-Owned Enterprises (Bumdes) in Receiving Aid at the Bengkulu Province Community and Village Empowerment Service was created using the Visual Basic .Net programming language. Based on the tests that have been carried out, the application is running well according to design